SpCas9-expression by tumor cells can cause T cell-dependent tumor rejection in immunocompetent mice. (4th May 2019) - Ajina, Reham; Zamalin, Danielle; Zuo, Annie; Moussa, Maha; Catalfamo, Marta; Jablonski, Sandra A.; Weiner, Louis M.
ABSTRACT: The CRISPR/Cas9 system has recently emerged as a highly efficient modality in genetic engineering and has been widely considered for various therapeutic applications. However, since the effector protein, SpCas9, has a bacterial origin, its immunogenicity must be explored in further depth. Here, we found that the intact immune system, in wild-type C57BL/6J and BALB/cL mice, stimulates specific immune response against SpCas9, resulting in the rejection of SpCas9-expressing tumors. However, these tumors effectively grew in syngeneic C57BL/6J immunodeficient, T cell-depleted and Cas9-KI mice. Therefore, these observations suggest that this tumor rejection phenotype is T cell-dependent. The immunological clearance of SpCas9-expressing tumors in the immunocompetent group illustrates the possibility of misinterpreting the impact of CRISPR/Cas9-mediated gene editing on in vivo tumor biology and survival. Thus, these findings have important implications for the use of this exciting approach in in vivo studies, as well as to manipulate cancer cell biology for therapeutic applications.